Zeolite membranes – a review and comparison with MOFs. (9th July 2015) - Rangnekar, N.; Mittal, N.; Elyassi, B.; Caro, J.; Tsapatsis, M.
Abstract : The latest developments in zeolite and MOF membranes are reviewed, with an emphasis on synthesis techniques. Industrial applications, hydrothermal stability, polymer-supported and mixed matrix membranes are some of the aspects discussed. Abstract : The latest developments in zeolite membranes are reviewed, with an emphasis on the synthesis techniques, including seed assembly and secondary growth methods. This review also discusses the current industrial applications of zeolite membranes, the feasibility of their use in membrane reactors and their hydrothermal stability. Finally, zeolite membranes are compared with metal–organic framework (MOF) membranes and the latest advancements in MOF and mixed matrix membranes are highlighted.